Penerapan Media Roda Putar untuk Meningkatkan Gramatika Bahasa Arab di MA Assunniyyah Kencong - Furoidah, Asni (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
Abstract Arabic grammar is the science of legislation and rules in Arabic or better known as nahwu and shorof. Learning Arabic grammar for students is not easy, boring learning and containing memorizing materials makes students' interest in learning and students' abilities in learning materials decrease. The use of rotary wheel media can help students improve Arabic grammatical skills. This study aims to describe the application of the rotating wheel media to improve Arabic grammatical skills. The results of the application of this rotating wheel show that the majority of students are capable of learning Arabic grammar based on assessment indicators. This rotary wheel media can be used as an alternative media in Arabic learning to improve Arabic grammar skills for students.